2003
DOI: 10.1021/ma034144k
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Dynamics in Miscible Polymer Blends:  Modeling the Combined Effects of Chain Connectivity and Concentration Fluctuations

Abstract: The dynamic heterogeneity of the segmental dynamics in miscible polymer blends has been alternatively interpreted in terms of either chain connectivity effects or thermal concentration fluctuations. Taking into account that both phenomena seem to be relevant, in this work we propose a minimal model which combines these two effects. This model basically assumes the self-concentration approach recently proposed by Lodge and McLeish [Macromolecules 2000, 33, 5278] and introduces a distribution of the effective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
114
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(117 citation statements)
references
References 25 publications
2
114
1
Order By: Relevance
“…Its limitations have led to modifications entailing additional parameters. 54 As seen in Figure 2, eq 2 overestimates T g for the blends by e10%. Also included in the figure are DSC results 55 for a PPO/PS blend of comparable molecular weights.…”
mentioning
confidence: 80%
“…Its limitations have led to modifications entailing additional parameters. 54 As seen in Figure 2, eq 2 overestimates T g for the blends by e10%. Also included in the figure are DSC results 55 for a PPO/PS blend of comparable molecular weights.…”
mentioning
confidence: 80%
“…These models attempt to explain the dynamical response of miscible polymer blends and the perplexing behavior of the lower T g component by considering heterogeneity in the composition of the local environment of polymer segments and local structure (e.g., density fluctuations, chain connectivity, etc.). While it has been shown that parameters of these models can be fitted to quantitatively reproduce composition and temperature dependence of segmental relaxation times for variety of miscible polymer blends, 31,32,36,37 there are number of blends in which these models are able to predict only qualitative trends observed in experiments 32,34 or fail completely, 36,38 indicating that some physics of segmental relaxation in polymers blends might be missing in those models.…”
Section: A-and B-relaxation Processes In Miscible Polymer Blendsmentioning
confidence: 99%
“…In a recent work, Leroy et al have treated the variance as a fitting parameter in accounting for the spectral width of dielectric relaxation data in polymer blends. 12 However, Salaniwal et al 9 have addressed this problem by estimating variances in local composition using the random phase approximation (RPA) applied to the contents of a finite spherical volume. This yields an integral expression involving the RPA structure factor that must be evaluated numerically.…”
Section: Alternative Estimate Of Variancementioning
confidence: 99%